Biochemical profile differences during the transition period based on different levels of non-esterified fatty acids at 7 weeks before parturition in Mediterranean Italian dairy buffaloes (Bubalus bubalis) - Lisuzzo, Anastasia; Mazzotta, Elisa; Cappelli, Giovanna; Martucciello, Alessandra; Monteiro, Bruno Moura; Sales, José Nélio Sousa; Di Vuolo, Gabriele; De Donato, Immacolata; Schiavo, Lorena; De Carlo, Esterina; Rossi, Pasquale; Contiero, Barbara; et al. (Frontiers in Veterinary Science, 2024)
Metabolic adaptations to negative energy balance, as well as lipomobilization, influence inflammatory responses, immune function, and oxidative stress in animals. This study aimed to evaluate the biochemical profile of Mediterranean buffaloes with different levels of lipomobilization from the prepartum to the postpartum period. A total of 76 Mediterranean buffaloes were enrolled, and a weekly blood sample was taken from 7 weeks before to 6 weeks after calving. The concentration of non-esterified fatty acids (NEFAs) was determined in serum and was used to categorize buffaloes into three lipomobilization groups 7 weeks before calving: mild (NEFA-I; NEFA ≤ 0.29 mEq/L; n = 18), medium (NEFA-II; 0.29 < NEFA < 0.57 mEq/L; n = 20), and severe (NEFA-III; NEFA ≥ 0.57 mEq/L; n = 38). Two-way repeated measures ANOVA was used to assess changes within and between the groups and over time. Significant differences were found in the concentration levels of NEFA, β-hydroxybutyrate, glucose, cholesterol, protein profile, oxygen radicals, antioxidants, lysozyme, complement, and minerals. These results suggest that both medium and severe lipomobilization groups are associated with metabolic alterations. In conclusion, buffaloes with higher NEFA levels (>0.29 mEq/L; NEFA-II and NEFA-III) at 7 weeks before calving should be monitored more closely to reduce the risk of metabolic diseases. Furthermore, the medium (NEFA-II) and severe (NEFA-III) lipomobilization groups could be associated with differences in the animals’ ability to manage their metabolic status. Specifically, the severe mobilization group was most associated with a greater energy deficit during both the prepartum and postpartum periods without oxidative stress. On the contrary, the medium mobilization group was associated with a less severe energy deficit but was also associated with an inflammatory status and oxidative stress during the prepartum period. These distinctions highlight the need for tailored management strategies to address varying levels of metabolic stress in dairy buffaloes.